(untitled) (Third Sector Social Economic Review, 2019)
Greenhouse gas emissions, which have become one of today’s leading environmental problems, have increased worldwide, especially in the industrialized countries, with the industrial revolution. Another reflection of the industrialization process is the excessive use of resources limited in nature. These two important conditions, such as environmental pollution, global warming, climate change, lack of natural resources, bring many dangers for both the present generations and future generations. Countries are focused on environmental policies to protect natural resources and achieve sustainable development, as it is highly likely that permanent changes that threaten the world will occur if necessary measures are not taken to prevent these and other hazards. In this context, especially in recent years, countries tend to have policy instruments that are consistent with their environmental policies. Carbon tax, which is one of these policy instruments, is one of the notable topics in both national and international studies. However, the carbon tax being implemented in some countries in the world have not yet implemented in Turkey. In this study, carbon tax is handled comprehensively. In this regard, the purpose of a carbon tax in the process of carrying out the work in terms of sustainable development as a proposal to offer Turkey a new policy tool and to discuss the feasibility of carbon taxes in Turkey. Combating climate change in operating results and sustainable development in the process of realization of the Turkey determined that the existing policy instruments routers and controllers is poor direction, provided to intensify control mechanisms in this regard has been determined that the need for a new economic tools.